Effects of Dietary Lipid Levels on Growth, Digestive Enzyme Activities, Antioxidant Capacity, and Lipid Metabolism in Turbot (Scophthalmus maximus L.) at Three Different Stages. (20th June 2022) - Zhang, Wencong; Dan, Zhijie; Zhuang, Yanwen; Zheng, Jichang; Gong, Ye; Liu, Yongtao; Mai, Kangsen; Ai, Qinghui
Abstract : Three 56-day feeding trials were conducted to evaluate dietary lipid requirements and effects of dietary lipid levels on growth, digestive enzyme activities, antioxidant capacity, and lipid metabolism in turbot ( Scophthalmus maximus L. ) at three growth stages. The initial mean body weight of turbot was 9.13 ± 0.17  g, 50.10 ± 0.38  g, and 80.05 ± 0.76  g (small, medium, and large turbot), respectively. Five practical diets were formulated to contain 68.4, 93.9, 120.7, 147.8, and 171.2 g/kg lipid (L68.4, L93.9, L120.7, L147.8, and L171.2), respectively. Results of three trials showed that the weight gain rate and specific growth rate of turbot fed with L120.7, L147.8, and L171.2 diets were all significantly higher compared with turbot fed with L68.4 and L93.9 diets except for large turbot fed with the L147.8 diet. Activities of intestinal trypsin, lipase and hepatic catalase, superoxide dismutase, and total antioxidant capacity firstly increased and then decreased as dietary lipids increased. Meanwhile, malondialdehyde content decreased firstly but then increased with the elevation of dietary lipids in small and medium turbot, and it was significantly higher in the L171.2 group than the rest in large turbot. With increasing levels of dietary lipid, contents of whole-body lipid, liver lipid, serum total cholesterol, triglyceride, and low-density lipoprotein cholesterol were markedly increased at three stages. In addition, serum high-density lipoprotein cholesterol contents increased firstly and then decreased over the L120.7 group. Transcriptional levels of lipolysis-related genes lipin1 and lpl were significantly upregulated firstly and subsequently downregulated with increasing dietary lipid levels except lipin1 in medium fish. Meanwhile, a significant increase in lipogenesis-related genes lxr and pparγ expressions was detected in all fish. Based on the specific growth rate, the dietary lipid level of 130.1, 120.1, and 107.7 g/kg was optimal for the growth performance of turbot cultured at three phases, respectively. Additionally, the results indicated that high lipid diets may lead to abnormal lipid deposition and affect the physiological health of turbot.